Sexual harassment prevention program for Indonesian nursing aides: a mixed-methods study - Eva Berthy Tallutondok; Chia-Jung Hsieh; Ya-Ling Shih; Satriya Pranata (Intelektual Pustaka Media Utama, 2023)
Available evidence suggests that sexual harassment is widespread among Indonesian nurse aids working overseas, however little research has been done on the topic. This study investigated the effectiveness of sexual harassment prevention program for Indonesian foreign nursing aides working in long term care in Taiwan. Average work experience was 54.8 months and 93% of participants were female. We used mixed methods followed by a focus group. Quantitative data were analyzed using Wilcoxon signed rank test. Most participants had higher post-test scores, indicating a significant positive change in their awareness about sexual harassment (effect size r=0.84). More work experience correlated with less sexual harassment and greater job satisfaction. Content analysis was used to analyze qualitative data. Four themes emerged from the discussion: harassment may not be intentional, perpetrators are male patients, communicating in an effective and timely manner is important, and personal safety on the job is a concern. Although sexual harassment prevention programs are important for nurse aides, these programs should also include patients, their families, and staff members at long term care facilities. Further recommend the Indonesian Economic and Trade Office in Taiwan collaborate with private agencies to provide legal protection and training programs on these issues.